Implementasi Kompetensi Kepribadian Guru Mata Pelajaran Agama Islam dalam Meningkatkan Akhlak Mulia Siswa pada Madrasah Aliyah Negeri 2 Watampone - Sumarni, Sumarni (JURNAL AL-QAYYIMAH, 2019)
This article examines the personality competency implementation of Islamic religious subjects in enhancing the students ' noble character in Madrasah Aliyah Negeri 2 Watampone. The study uses a type of field research with qualitative descriptive analysis. The results showed that, 1) the personality competence of Islamic religious subjects in Madrasah Aliya Negeri 2 Watampone can be understood that, the teacher acts in accordance with the national religious, legal, social, and cultural norms of Indonesia. Presenting itself as an honest, noble-worthy person, and an example for students and the community. Presenting itself as a steady, stable, mature, expedient, and authoritative person. Demonstrate a work ethic, high responsibility, a sense of pride to be a teacher, and a sense of self-confidence. Uphold the teacher's code of ethics. 2) The efforts of teachers of Islamic religious subjects to improve the students ' noble, including, transparency, habituation, advice and motivation, story.